Seroprevalence of mycoplasmosis in broiler, layer, and native chickens in Giza, Egypt. - Saeed El-Ashram; Mahmoud E Hashad; G A Abdel-Alim; Taher Abdelhamid; Heba N Deif (PLoS ONE, 2021)
We aimed to investigate Mycoplasma infections among chicken flocks (Ross, Lohmann and native) in Giza, Egypt, using serological tests, including the slide plate agglutination (SPA) test, hemagglutination inhibition (HI) test, and enzyme-linked immunosorbent assay (ELISA). The slide plate agglutination examination, a serological test, indicated the prevalence of Mg and Ms infections of 10.9% and 13.2%, respectively. On 91 SPA test positive serum samples for either Mg or Ms, a passive hemagglutination/hemagglutination inhibition (HI) test was performed. The SPA and HI test findings were found to be comparable. On 90 SPA test positive samples, an ELISA was performed using commercial kits for Mg and Ms serodiagnosis. According to the ELISA data, only 83.33% and 18.88% of SPA test positive samples were confirmed as positive for Ms and Mg infections, respectively. The prevalence increased to 84.44% and 77.77%, respectively, when suspected samples were deemed positive.